COVID-19 Vaccine Booster Acceptance in The Work Area of Baumata Health Center - Chandraningsih, Ni Putu Angelisa; Adu, Apris A.; Ndoen, Honey Ivone (Media Kesehatan Masyarakat, 2023)
The COVID-19 booster vaccine is a follow-up vaccine given to individuals after receiving the complete primary COVID-19 vaccine to improve effectiveness and increase the individual's level of immunity to extend the protection period against COVID-19 infection. However, some people are still unsure about the booster. This study aims to determine the acceptance of the COVID-19 booster vaccine in the work area of Baumata Health Center. This research was descriptive, using a rapid survey method. The sample size was 210 respondents and was selected using a two-stage cluster sampling technique. The research results illustrated that respondents' knowledge regarding booster vaccines is quite good (50%), the level of trust in booster vaccines is classified as doubtful (49.05%), and the public's attitude regarding booster vaccines is quite good (65.24%). Respondents refused the booster because COVID-19 was considered no longer present. Public knowledge needs to be increased to improve people's belief and attitude towards receiving the vaccine.